The population genetics of green mussel (perna viridis) from Sabah, Malaysia and implication to its aquaculture - Lau, Jen Shi (2016)
The extraordinary growth performance and simple culture method of green mussel (Pema viridis) make it a potentially profitable aquaculture species. However, green mussel aquaculture in Sabah still relatively undeveloped. As green mussel aquaculture in Sabah is completely relying on wild green mussel population for both spats and broodstock, It is imperative to understand various population parameters of green mussel including the population genetic Information before green mussel aquaculture improvement initiatives commence. In this study, 200 green mussel specimens were collected from five locations in Sabah which included Kota Kinabalu, Kota Marudu, Kuala Penyu, Tuaran and Tawau. The population genetic of green mussel in Sabah was examined using mitochondrial DNA (D-loop) and microsatellite W. Fifteen microsatellite loci were examined using polyacrylamide gel electrophoresis whereas mitochondrial DNA (d-loop) was examined using DNA sequencing method. Standard genetic diversity indices for mitochondrial DNA were calculatedI n DnaSP5.10.1w here as micro satellite was calculated in Ariequin3 .5.1.2. Pairwise F-statistic, AMOVA and Mantel's test were calculated for both D-loop and microsatellite using the Ariequin 3.5.1.2. Nested lade analysis, UPGMA dendrogram and STUCTURE2 .3.4 were used to further elucidate the population structure of the green mussel. Besides, genetic bottleneck signature in the green mussel population was examined using BOTTLENEC1K. 2.02 and neutral tests in Arlequin 3.5.1.2. Green mussel population showed high haplotype diversity and low nudeotide diversity (Hd=0.916; n=0.00915) in mitochondrial D-loop region whereas the microsatellite genetic diversity of green mussel in Sabah (A=3.08; He=0.43) was lower than other location such as Thailand. The low average allele number indicated the adaptability of the green mussel population to sudden change in environment and disease outbreak is weak. Introduction of green mussel stocks from Thailand would probably increase the genetic diversity of the green mussel population in Sabah and may manifest the genetic differences in commercially significant phenotypic traits. AMOVA and pairwise F-statistic for both microsatellite and D-loop showed low but significant population structuring. Nested Glade analysis based on mitochondrial DNA was unable to Identify the population structure clearly. However, STRUCTURE and UPGMA dendrogram based on microsatellite data showed that the individuals from Kota Marudu and Tawau constituted a cluster whereas individuals from Kota Kinabalu, Kuala Penyu and Tuaran formed the another duster. The population structure pattern was probably affected by local marine current, larvae behaviour or even anthropogenic activities. From fisheries management perspective, it is desirable to manage the two groups separately. Significant genetic bottleneck signature was not detected In either microsatellite loci or D-loop of mitochondrial DNA albeit green mussel population in Sabah passed through a severe mass mortality which lasted for almost three years. In conclusion, the outcomes of this study have created a sound foundation for green mussel aquaculture improvement program in Sabah